2019
DOI: 10.1007/s42380-019-00058-y
|View full text |Cite
|
Sign up to set email alerts
|

Forms of Bullying and Associations Between School Perceptions and Being Bullied Among Finnish Secondary School Students Aged 13 and 15

Abstract: The study aimed to examine the extent to which Finnish secondary school students experience bullying, how they are bullied, and whether being bullied is associated with school perceptions. The analyses were based on data from the Finnish part of the international Health Behaviour in School-aged Children (HBSC) study, and were obtained from 4262 students aged 13 and 15. The sample was nationally representative. Logistic regression analysis was performed to identify the associations between school perceptions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(56 reference statements)
4
12
0
Order By: Relevance
“…Research by Caprara et al [52] suggests that this dimension of aggression is higher and more stable over time in girls, while in boys it decreases with age. It is surprising that boys scored higher than girls on the indirect aggression scale, which is not in line with other research [7,50]. This discrepancy could be explained by referring to the results of a metaanalysis conducted by Card et al [51], which showed that boys score higher on indirect aggression in self-report studies, while girls score higher in studies using objective assessments (from teachers and parents).…”
Section: Resiliency As a Mediator Between Aggressiveness And Average mentioning
confidence: 79%
See 1 more Smart Citation
“…Research by Caprara et al [52] suggests that this dimension of aggression is higher and more stable over time in girls, while in boys it decreases with age. It is surprising that boys scored higher than girls on the indirect aggression scale, which is not in line with other research [7,50]. This discrepancy could be explained by referring to the results of a metaanalysis conducted by Card et al [51], which showed that boys score higher on indirect aggression in self-report studies, while girls score higher in studies using objective assessments (from teachers and parents).…”
Section: Resiliency As a Mediator Between Aggressiveness And Average mentioning
confidence: 79%
“…According to International Health Behaviour in School-aged Children (HBSC) research, there has been a decrease in aggressive behaviors (operationalized as taking part in bullying classmates [5]), but this remains one of the most urgent problems in schools [6]. Research shows that the most common aggressive behavior at school is verbal teasing and that girls are more indirect, while boys usually use physical bullying [7]. Aggressive behavior is a signi cant risk factor that increases the likelihood of teenagers adopting rule-breaking behaviors [8], which are associated with lower school achievement [9] and even failure to graduate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of bullying behaviors recruited male students more than females [ 30 32 ], but an equal number of boys and girls was recruited by [ 33 ]. Several studies investigated bullying among children 11–15 years old [ 31 , 33 – 35 ]. Other studies were conducted among higher age groups of 12–18 years [ 30 , 32 , 36 ] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with [ 32 ], who reported that verbal bullying was most common, followed by social and then physical bullying among US adolescents from grade 6 to grade 10 . Similarly, a study on forms of bullying among secondary school students aged 13 and 15 in Finland found that the most common forms of bullying were verbal teasing and social exclusion [ 31 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Bullying is a form of violence that endangers well-being of children, youth and adults (Markkanen et al, 2019). A person is a victim of bullying when he or she is exposed by one or more individual repeatedly over time to any unwanted aggressive behavior(s) and is unable to defend him or herself, excluding situations in which two individuals with equal physical and psychological bullying are the bully (bullying behavior perpetrator); the victim (bullying behavior recipient); the bully/ victim (victim and perpetrator); and the bystander (bullying behavior witness) include peer victimization in which a student or group of students bullies an individual peer or group of peers; teacher-on-student bullying is when a teacher bullies a student; and studenton-teacher bullying in which a student bullies a teacher (Markkanen et al, 2019). The most serious consequence of school bullying is deterioration in academic performance due to the perception and avoidance of school as an unsafe place, presence of low selfesteem and isolation that is carried to adulthood (Kazarian and Ammar, 2013).…”
mentioning
confidence: 99%